"And I'll Only be Killed by a Peer". (2nd January 2017) - Surat, Irina
Abstract : In a less formal article, Irina Surat parses the words and history of Osip Mandelstam's poem "The Wolf, " mostly written in 1930, to identify the significance of its final line, which the poet settled on only in 1935. The discussion ends by citing a stanza from "Facing Nature, " a 1975 poem by Aleksandr Eremenko, which builds on Mandelstam's poem in much the same way as Mandelstam's builds on writings by Nikolai Gumilev and Aleksandr Pushkin.